Stephen Cooper, Clorinda Donato, Eds., "John Fante’s ‘Ask the Dust’. A Joining of Voices and Views" (ENTHYMEMA, 2020)
Review of Stephen Cooper, Clorinda Donato, Eds., John Fante’s ‘Ask the Dust’. A Joining of Voices and Views. Fordham UP, New York, 2020.
Keywords: John Fante; Ask the Dust; Los Angeles; Contemporary U.S. Literature